Assessing the Efficacy of Intermittent Intensive Physical Therapy in Pediatric Cerebral Palsy - Rekha, Chitrada; M., Kamalakannan; Senthilkumar, Natarajan; Varsha, Anbu; Akshaya, Venkat; B.S., Shathurshini; M., Sai Nikesh; V., Sri Kanth (INTI International University, 2024)
Background: Cerebral palsy (CP) is a prevalent neurological disorder affecting children worldwide, particularly boys, with spastic CP being the most common form. Despite its prevalence, effective rehabilitation strategies for severely disabled children with CP remain limited. Objective: This study aimed to evaluate the feasibility and effectiveness of a 6-month rehabilitation program for severely disabled children with CP, utilizing alternating intense therapy sessions and rest periods, to enhance gross motor function. Methods: Employing a multiple-baseline design, the study assessed changes in motor performance using the Gross Motor Function Measure (GMFM). Visual and statistical analyses, including descriptive statistics and paired t-tests, were conducted to evaluate outcomes. Results: Participants received an average of 60 treatments over the 20-week trial, exceeding expectations. Seven out of ten children exhibited significant increases in GMFM scores, with a mean improvement of 9.2% (range 3 to 15%; p < 0.05). Importantly, all participants maintained motor function during rest periods, with a high compliance rate of 93.1% during intense therapy. Conclusion: The study highlights the potential of the proposed rehabilitation program to improve gross motor function in severely disabled children with CP. These findings provide valuable insights for developing more effective and sustainable rehabilitation strategies for this population.